Stimulus range bias leads to different settings when using luminance adjustment to evaluate discomfort due to glare. (15th April 2019) - Kent, M.G.; Fotios, S.; Cheung, T.
Abstract: Luminance adjustment is widely used to evaluate discomfort due to glare. This paper reports an experiment conducted to investigate two factors of the luminance adjustment procedure, stimulus range bias and direct vs indirect control. Stimulus range bias describes the influence on subjective evaluations of the range of stimuli available to the test observer, with range being the minimum and maximum available glare source luminance in the current context. For the glare source, an artificial window, there were three ranges, having maximum luminances of 5 106, 7288 and 9469 cd/m 2 . The results suggest that luminance range had a significant effect on settings made, sufficient to change settings by an amount equivalent to one step of a Hopkinson-like discomfort sensation scale. The mean luminance associated with just intolerable discomfort with the low range was less than that associated with just uncomfortable with the high range. Past experiments have used direct control, where the observer makes the adjustment directly, and indirect control, where the observer instructs the experimenter to make the adjustment actions. Both methods were used in the current experiment. It was found that range bias was larger when using direct control than with indirect control. These findings contribute to an understanding of why different studies of discomfort glare have reported different results and hence proposed different discomfort models. Graphical abstract: Image 1 Highlights: Stimulus range bias in an adjustment procedure was evaluated using three different ranges of luminance. The influence of control was evaluated using direct (participant) and indirect (experimenter) control to make adjustments. Larger luminance ranges led to higher glare settings for the same discomfort sensation. The range bias effect was larger when direct control was used. Stimulus range bias could explain the inconsistencies found across glare studies.